2016
DOI: 10.3832/ifor1389-008
|View full text |Cite
|
Sign up to set email alerts
|

Developing a stand-based growth and yield model for Thuya (Tetraclinis articulata (Vahl) Mast) in Tunisia

Abstract: (2) Thuya (Tetraclinis articulata (Vahl) Mast) is a Mediterranean forest species mainly occupying semiarid environments in North African countries, where it provides important ecological and economical services, such as biodiversity conservation, soil protection against erosion, fuelwood, timber for fencing, construction and handicraft, resins, etc. Despite the importance of the species, there is a severe lack of scientific knowledge as regards the management of these forests or modeling tools to support multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(23 reference statements)
0
8
0
1
Order By: Relevance
“…The developed model, used in conjunction with the previously developed models for tree level attributes (Calama et al 2012), the distance-independent individual tree diameter-increment model (Sghaier et al 2013) and the stand based growth and yield model presented in Sghaier et al (2015), constitutes a useful tool for the sustainable management of Tetraclinis articulata forests in north-east Tunisia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The developed model, used in conjunction with the previously developed models for tree level attributes (Calama et al 2012), the distance-independent individual tree diameter-increment model (Sghaier et al 2013) and the stand based growth and yield model presented in Sghaier et al (2015), constitutes a useful tool for the sustainable management of Tetraclinis articulata forests in north-east Tunisia.…”
Section: Resultsmentioning
confidence: 99%
“…The sum includes all diameter classes in the i-th plot. In this error index, we can multiply the absolute difference between the observed and predicted number of trees per diameter class by the volume, using an equation developed by Sghaier et al (2015) This index can also be expressed relatively as a percentage by dividing it by the total volume of the observed distribution in the plot (Lejeune 1994 -eqn. 19).…”
Section: Methods Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Sites on calcareous brown soil and rendzine correspond to fertility class 2, with a site index of 10.5 to 13.5 m for 50-year-old trees. Sghaier et al (2001) identified four classes of fertility, with a reference height of 45 years in descending order: class 1, with a reference height of 13.5 m; class 2, with a reference height of 10.5 m; class 3, with a reference height of 7.5 m; and class 4, with a reference height of 4.5 m. The authors concluded that about 49% of Aleppo pine stands in Tunisia belong to fertility class 3. Akrimi (1984) and Garchi (1991) studied the production of Aleppo pine in northwestern Tunisia (Sakiet region), showing that the most important production was between 0.4 and 4 m 3 ha -1 yr -1 for a dominant height (9.7-22.8 m).…”
Section: Productivity and Growth Of Aleppo Pine Forestsmentioning
confidence: 99%